Different Approaches to Model Cover-Cracking of RC Structures due to Corrosion - Roshan, Arman (Université d'Ottawa / University of Ottawa, 2018)
This thesis presents three different approaches to model corrosion-induced crack propagation in reinforced concrete structures. The first approach is solved numerically using finite differences to model the softening behaviour of concrete in tension. The second approach idealizes the concrete cover as either a brittle elastic or an elastoplastic material so that it may be solved using a closed-form solution. Both approaches are based on a thick-walled cylinder (TWC) analogy and consider rust compressibility and rust diffusion into cracks. The third approach uses finite element modelling to validate the application of the TWC and perform a parametric study. The results obtained using each approach are compared against each other as well as against experimental results. The TWC was found to be an appropriate analogy for the geometries and reinforcement configurations considered. Analytical models were found to provide upper and lower limits to the results based on the numerical model. The experimental data found in the literature showed reasonable agreement with predictions from the numerical and elastoplastic models.
Keywords: Corrosion; Modelling; Cover-Cracking; RC Structures; Thick-Walled Cylinder; Finite Differences; Finite Element; TWC; Rust Compressibility; Rust Diffusion; Critical Attack Penetration; Visual Critical Attack Penetration; Elasto Plastic Cylinder; Brittle Elastic Cylinder; Maximum Internal Pressure